A decision support system for the university course timetabling problem at ISEP-DEM - Fernandes, Isa Lara da Silva (2024)
In this work, a decision support system (DSS) has been developed to support the creation of academic timetables at the Instituto Superior de Engenharia do Porto (ISEP), addressing the problem of university course timetabling. The DSS was designed to handle the scheduling of all years and regimes (day and evening) of undergraduate and postgraduate courses in the Department of Mechanical Engineering. The motivation behind this project was to automate and optimise the timetabling process, which is currently done manually at ISEP. This manual process is complex, time consuming and requires significant effort from the faculty to create schedules based on historical data. The solution used an integer mathematical programming approach, implemented using the Python programming language in conjunction with the CPLEX solver and the Pyomo library. The DSS was designed to integrate real-world data and handle a variety of constraints and preferences from both faculty and students. It aimed to reduce the time and human resources required to create the timetable. The results show that the DSS provides feasible and efficient solutions for timetabling, significantly improving the resource allocation process and reducing manual effort. The successful implementation for two specific degrees suggests that the approach can be further developed to meet the scheduling needs of all degrees at ISEP, ultimately streamlining the scheduling process and meeting future demands.